Corrosion failure analysis of CuNi 90/10 on seawater fire protection system - Riastuti, Rini; Alfian, Alfian; Manurung, Rizky Rama Putra; Budiarto, Wahyu; Kaban, Agus S (Jurnal Pendidikan Teknologi Kejuruan, 2022)
The failure analysis of a seawater fire protection system of oil and gas processing facility was observed in this paper. The fire protection pipe line & hull seawater filter were made of CuNi 90/10. Severe deep pits and fracture were observed at bottom of jockey pump spool pipe and hull seawater filter. Visual observation, scanning electron microscope, energy dispersive spectroscopy, x-ray diffractometry were employed in the present failure analysis. The oxygen exposure on CuNi 90/10 of Seawater Fire Protection system had a significant impact on failure and was exacerbated by the presence of chloride exposure.